Pengaruh Pendidikan Kesehatan dengan Media Poster terhadap Pengetahuan Manajemen Hipertensi pada Penderita Hipertensi - Ulya, Zakiyatul; Iskandar, Asep; Triasih, Fajar (Jurnal Keperawatan Soedirman, 2017)
The low hypertension management knowledg causes uncontrolled high blood pressure and it's complication. A health education may increase the hypertension management knowledge. Poster is one of the health education media consisting letters, picture, and can be patch anywhere, so it can be read repeatedly. This was a quasy experiment with pre and post-test non equivalent control group design. This study recruited the respondents using a consecutive sampling method. The sample size was 32 respondents which divided into intervention and control group. The data were analyzed using Paired t-test and Independent t-test. The majority of respondents were age between 45-60 years old, female, housewife, and graduated elementary school. The Paired t-test results showed that there were significant differences of the knowledge pre and post-test scores in the intervention group (p = 0,000) and control group (p = 0,194). The Independent t-test results showed that there were significant differences between the knowledge post-test scores among the intervention group and control group (p= 0,016). Health education using posters may improve the hypertension management knowledge among the hypertension patients.